2001
DOI: 10.2320/jinstmet1952.65.11_1023
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Crystallographic Structure of Electrodeposited Ni-W Alloy Film and Its Thermal Equilibrium Diagram

Abstract: Electrodeposited Ni W alloy films were obtained from Nickel Sulfate baths containing Na 2 WO 4 . The crystallographic structure and morphology of electrodeposited Ni W films were studied by XRD, HRTEM, SEM and heat treatment technique. The crystallographic structures of electrodeposited Ni W alloy films were also compared with the Ni W thermal equilibrium diagram.The X ray diffraction patterns of Ni W electrodeposited films with various W contents gradually changed from sharp peaks to broad peaks with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
2
8
0
1
Order By: Relevance
“…21) Furthermore, with regard to the P composition range for forming amorphous in the deposited films, Masumoto et al concluded that the P composition range for forming the amorphous phase should surround the P composition of eutectic point since around this composition, the deposited films can be quenched most readily with the lowest energy. 22) However, many experimental results [23][24][25][26] obtained by our laboratory including the result of the present study, have proved that the P composition range for forming the amorphous phase should surround the composition range for forming the intermetallic compound.…”
Section: Amorphous Phase Formation In the Deposited Filmsmentioning
confidence: 86%
“…21) Furthermore, with regard to the P composition range for forming amorphous in the deposited films, Masumoto et al concluded that the P composition range for forming the amorphous phase should surround the P composition of eutectic point since around this composition, the deposited films can be quenched most readily with the lowest energy. 22) However, many experimental results [23][24][25][26] obtained by our laboratory including the result of the present study, have proved that the P composition range for forming the amorphous phase should surround the composition range for forming the intermetallic compound.…”
Section: Amorphous Phase Formation In the Deposited Filmsmentioning
confidence: 86%
“…As mentioned before, it has been reported that the electrodeposited Ni-W alloy has single amorphous phase in the W-concentration range above 20 at%. 4,5) It has also been reported that the grain size of 2 nm is the size where intercrystalline regions (grain boundaries, triple junctions, and quadruple nodes) constitute the entire microstructure, and the material can be regarded as essentially amorphous. 17,20,21) Then, the W-concentration of more than 25% is chosen in this study.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the electrodeposited Ni-W alloy has single amorphous phase in the W-concentration range above 20 at%. 4,5) However, it has been clarified from three dimensional atom probe analyses and the nano-beam diffraction patterns that if the Wconcentration decreases only 2.2 at% from 20 at%, the material shows the amorphous/nanocrystalline duplex structure with the volume fraction of amorphous phases of 63.4%. 6) This result indicates that the small W-concentration fluctuation causes the considerable change of volume fraction of the amorphous phase in the composition around the Wconcentration of 20%, which can significantly affect the scattering of the strength.…”
Section: Introductionmentioning
confidence: 99%
“…In electrodeposited Ni-W alloys, it has been generally recognized that the structure changes from the single nanocrystalline (fcc Ni solid solution) phase to single amorphous phase at the W concentration of around 20 at%. 11,12) The conceptual model of grain-boundary phase has been employed to describe the dependence of the mechanical property on the grain size. The composite model 13,14) explains that Hall-Petch breakdown is attributed to the increased volume fraction of a comparably soft grain boundary phase as the grain size decreases.…”
Section: Introductionmentioning
confidence: 99%